EVALUATION OF SERUM AND SALIVARY CA-125 IN BREAST CANCER PATIENTS – AN ANALYTICAL STUDY - DWIVEDI, URVASHEE; JAIN, ANURAG; ALI, FATIMA BHOPALWALA; Ali, Mustafa (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Breast cancer in females is very frequent nowadays both in developed and developing countries. Many tests both invasive and non-invasive are available for the diagnosis of cancer breast. Tumor markers are the substances that are associated with tumors and help in the detection and follow-up. Cancer antigen 125 (CA-125) is one of the tumor markers, the level of which increases in many tumors including breast cancer. Methods: The present study was carried out to quantitatively measure its level by enzyme-linked immunosorbent assay in the serum and saliva of known breast cancer patients and comparing it with control groups. Results: Statistically significant role of CA-125 in cases of breast cancer was ascertained over the control group and also positive correlation was found between serum and salivary values of CA-125. Conclusion: We conclude that CA-125 can be used as tumor markers in breast cancer patients for evaluation and salivary samples are equally effective as serum samples and also are easy and safe to obtain.